Field hospital : the church's engagement with a wounded world - Cavanaugh, William T., 1962- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2016)
Pope Francis in a 2013 interview famously likened the church to a field hospital. In this book William Cavanaugh adopts Pope Francis's metaphor to show how the church can help heal both the spiritual and the material wounds of the world. As he examines the intersection of theology with themes of religious freedom, economic injustice, religious violence, and other pressing topics, Cavanaugh emphasizes that the church cannot condemn the evils of the world from a position of superiority. Rather, he says, its practices of solidarity with humanity must be based on a profound recognition that the church shares in the guilt of human sin. Cavanaugh's Field Hospital provides guideposts for a church that is willing to go outside of itself onto today's battlefields -- both metaphorical and literal -- not to inflict wounds but to bind them up and heal them.
Markets and bodies -- Dispersed political theology -- Further explorations in religion and violence.
Includes bibliographical references and index.
Keywords: Mission of the church; Catholic Church -- Doctrines; Catholic Church